Consulting business startup - Sandburg, Sabrina Louise (Kansas State University, 2008)
Most of our education in college is focused on producing students that will graduate and go on to work for someone else. Most classes taken in college are based on theory and technical subjects, which are very important to understand. Where the education falls short on is showing the opportunity of owning and running your own business. This report describes basic steps necessary to start up a consulting business. The report concentrates on the challenges involved, deciding on the right type of business ownership, location and equipment, and extensively on the business plan. Engineering is typically considered a technical field with little interaction with people, which is only half right. There is a lot of interaction between the engineer and the architect, client, contractor, and any other consultants for any particular project. This report will also talk about relationships and how to convey a professional image. The emphasis of this report is to describe basic steps to get started on owning your own company.
Keywords: Engineering; Consultant; Business; Startup; Engineering, General (0537)